Innovative techniques in evaluating the esophagus; imaging of esophageal morphology and function; and drugs for esophageal disease. (11th October 2013) - Neumann, Helmut; Neurath, Markus F.; Vieth, Michael; Lever, Frederiek M.; Meijer, Gert J.; Lips, Irene M.; McMahon, Barry P.; Ruurda, J.P.; van Hillegersberg, R.; Siersema, P.; Levine, Marc S.; Scharitzer, Martina; et al.
Abstract : This paper reporting on techniques for esophageal evaluation and imaging and drugs for esophageal disease includes commentaries on endoscopy techniques including dye‐based high‐resolution and dye‐less high‐definition endoscopy; the shift from CT to MRI guidance in tumor delineation for radiation therapy; the role of functional lumen imaging in measuring esophageal distensibility; electrical stimulation of the lower esophageal sphincter (LES) as an alternative to fundoduplication for treatment of gastroesophageal reflux disease (GERD); the morphological findings of reflux esophagitis and esophageal dysmotility on double‐contrast esophagography; the value of videofluoroscopy in assessing protecting mechanisms in patients with chronic reflux or swallowing disorders; targeting visceral hypersensitivity in the treatment of refractory GERD; and the symptoms and treatments of nighttime reflux and nocturnal acid breakthrough (NAB).